PENGEMBANGAN ALAT UKUR SUHU BERBASIS MIKROKONTROLER ARDUINO NANO SEBAGAI MEDIA PEMBELAJARAN PADA MATERI SUHU DAN KALOR - Ade Tri Detasari; Soka Hadiati; Eti Sukadi (Vidya Karya, 2022)
The development of temperature measuring instruments based on the Arduino nano microcontroler as a learning medium for temperature and heat materials aims to determine the feasibility based on the assessment of media experts and material experts and to determine student responses to its use. This study uses a 4D model consisting of data analysis stage, product design stage, product manufacturing stage and product validation and testing stages. This study tested the feasibility of learning media and the concept of temperature and heat by 2 media xpert validators and 1 material expert validator. In addition, this study also looked at student responses from 29 students at SMA Negeri 1 Sepauk, Sintang Regency to the use of learning media developed using a questionnaire. Based on the results of the assessment carried out by the media expert validator, it can be concluded that the temperature measuring instrument based on the Arduino nano microcontroler as a learning medium on temperature and heat material obtained an average score of 89.55% with a very feasible category and the results of the assessment carried out by the material expert validator obtained an average score of 87.5% with a very appropriate category. Student responses to the use of learning media obtained an average score of 90.8% with the category strongly agree.Pengembangan alat ukur suhu berbasis mikrokontroler arduino nano sebagai media pembelajaran pada materi suhu dan kalor bertujuan untuk mengetahui kelayakan berdasarkan penilaian ahli media dan ahli materi serta untuk mengetahui respon siswa terhadap penggunaannya. Penelitian ini menggunakan model 4D yang terdiri tahap analisis data, tahap desain produk, tahap pembuatan produk dan tahap validasi dan uji coba produk. Penelitian ini menguji kelayakan media pembelajaran dan kesesuaian konsep materi suhu dan kalor oleh 2 validator ahli media dan 1 validator ahli materi. Selain itu, penelitian ini juga melihat respon siswa dari 29 siswa di SMA Negeri 1 Sepauk Kabupaten Sintang terhadap penggunaan media pembelajaran yang dikembangkan menggunakan kuesioner. Berdasarkan hasil penilaian yang dilakukan oleh validator ahli media dapat disimpulkan bahwa alat ukur suhu berbasis mikrokontroler arduino nano sebagai media pembelajaran pada materi suhu dan kalor diperoleh skor rata-rata 89,55 % dengan kategori sangat layak dan hasil penilaian yang dilakukan oleh validator ahli materi memperoleh skor rata-rata 87,5 % dengan kategori sangat sesuai. Respon siswa terhadap penggunaan media pembelajaran memperoleh skor rata-rata 90,8 % dengan kategori sangat setuju.